The Beginnings of University English - Lawrie, A. author. aut Link
IX, 190 p.
Keywords: Drawing on previously unseen archival material, The Beginnings of University English explores the innovative and scholarly ways in which English literature was taught to extramural students in England during the fin de siècle, and sheds new light on the modern roots of tertiary-level English teaching.